A Novel Catalyst Ag/MgO-CeO2-Al2O3 for the Low-temperature Ethanol- SCR of NO Under Lean de-NOx Conditions - Valanidou, Lilian; Theologides, Christodoulos P.; Olympiou, Georgios; Savva, Petros G.; Costa, Costas (My University, 2012)
The present work reports data on a novel catalyst having excellent activity, selectivity and stability for the selective reduction of nitric oxide to nitrogen in the presence of ethanol or ethanol/hydrogen mixture as reducing agent, in the low temperature range of 150-300°C and in the presence of excess oxygen, H2O and SO2 in the feed. The novelty of the present catalyst compared to other patented ones, for the reaction at hand, lies upon the simplicity and the remarkably low Ag loading (wt%) used, characteristics that are required for a practical application. In addition, the latter catalyst shows significant activity (rate of NO reduction) at much lower temperatures (below 300°C) compared to other already patented catalysts. The present inventive catalyst consists of silver crystals that are in contact with a mixed oxide support comprised of MgO, CeO2 and Al2O3 in 1:1:2 wt% ratio. This novel catalyst presents high activity in terms of NO conversion (XNO = 60-90%) and high selectivities towards N2 (SN2 = 92-95%) and CO2 (SCO2 > 97%) in the range of 150-400°C, at a GHSV of 40,000 h-1 and using a feed stream of 0.05vol% NO, 0.1vol% EtOH, 5vol% O2 and 5vol% H2O. To our knowledge, this is the highest selectivity towards N2 and CO2 ever reported. In addition, the current catalyst shows remarkable stability with time on stream and in the presence of 5 vol% H2O and 50 ppm SO2 in the feed stream. After 48 h on stream the patented catalyst retains its stability expressed in high activity (XNO > 80%) and selectivities to N2 (SN2 > 95%) and CO2 (SCO2 > 97%).
Keywords: Ethanol; Oxides; Ethanol-SCR; HC-SCR; Lean de-NOx; NO reduction